Hearing Loss as a Risk Factor for Dementia [Hipoacusia Como Factor de Riesgo Para Demencia] - Wimmer-Del Solar, J (Sociedad Medica de Santiago, 2020)
In the last decades, there has been an increase in life expectancy in the world, with the consequent modification in the proportion of adults over 60 years. This is accompanied by an increase in pathologies for which aging is the main risk factor, such as dementia and hearing loss, which profoundly affect the quality of life of individuals and their family and impact health system costs. Given the lack of disease-modifying treatments for dementia, the study of mechanisms to prevent its occurrence has become a world priority. In the year 2017, the Lancet “Commission for dementia prevention, intervention, and care” proposed a model, in which hearing loss emerged as a new modifiable risk factor for the development of dementia. This result undoubtedly has important consequences for the understanding the multifactorial nature of dementia, our daily clinical practice and public policies aimed at its prevention and treatment. In this article, we review the current evidence supporting the association between dementia and hearing loss, discussing the available strategies for prevention, detection and treatment of hearing loss and its possible impact on the natural course of dementia. A flow chart for the clinical management of different subgroups of patients is proposed. © 2020 Sociedad Medica de Santiago. All rights reserved.